Hermenêutica constitucional concretista sob o paradigma do estado democrático brasileiro - Silva Júnior , Antônio Soares (2008)
This dissertation intends to analyze alternatives in adopting an interpretative theory targeting actual fundamental rights exercise in Brazilian democratic State. This research considered contributions from key authors in developing a Law’s hermeneutical perception which objective is to shorten distance and improve communication between the law’s must be and the be from social reality, promoting the development of a society regarding a diversity perspective in addition to the jurisdictional activity itself. Approach taken is in view of perspective of a diverse and complex society in which the official interpreter participates and the difficulties in deciding for each actual case. Furthermore, seeks uncovering some myths related to Brazilian fundamental rights exercise while confirming others in accordance with the theories herein, providing a general framework for a feasible interpretative activity by the judging part within an at the a first assessment unfavorable social scenario.